Preparation of SERS Substrates for the Detection of Organic Molecules at Low Concentration - Chi, Tran Thi Kim; Le, Nguyen Thi; Hien, Bui Thi Thu; Trung, Dang Quoc; Liem, Nguyen Quang (Communications in Physics, 2017)
In this paper, we present the results of the preparation of Surface Enhanced Raman Spectroscopy (SERS) substrates by depositing silver nanoparticles (Ag NPs) onto a porous silicon wafer that is produced by the chemical etching process. The influences of the preparation parameters such as resistivity of the silicon wafer, the anodizing current density, etching time to the size of pores were systematically investigated. The SERS substrates prepared were characterised by using appropriate techniques: the morphology and pores size by scanning electron microscope (SEM), the SERS activity by Raman scattering measure of organic molecules malachite green (MG) embedded into the substrate at room temperature. Our experimental results show that a home-made Raman microscope system could be efficiently used to detect the MG molecules at the concentration lower than 10-7 M with the prepared SERS substrates which have Ag NPs in the obtained pores of 10 – 40 nm.